Collective Action Towards Risk Management in Informal Urban Areas in Medellín: COVID-19 Lessons for Reducing Vulnerability and Inequality - Garcia Ferrari, Soledad; Crane De Narváez, Stephanie; Castro Mera, Wilmar Edgardo; Velásquez, Carlos; Bain, Amelia A. (Frontiers in Environmental Science, 2022)
Recent experiences of socio-environmental disasters in Latin America have demonstrated the ineffectiveness of the state as a social actor in the organisation, coordination and implementation of adequate public policies to face these emergencies. This affects the most vulnerable urban areas, leading to unequal levels of impact from crises and disasters within cities. As a response, local collective actions, led by citizens, have emerged to manage risks. In Medellín, Colombia, in the context of the current COVID-19 crisis, our research identified a diverse repertoire of collective actions within informal, vulnerable communities, including collaboration towards improving food security, sanitation, pedagogy for self-care and prevention, and financial aid. Although these actions have had limited scope within the context of the ongoing COVID-19 pandemic, they demonstrate the need to promote a more proactive interaction between society and the state, based on a series of agreed interventions, promoting the exchange of knowledge and articulation of actions in the production and improvement of informal urban areas. This research explores how these collective actions have developed through a set of semi-structured interviews with community leaders and key actors in Medellín, with a view to identifying lessons for state-community dynamics in relation to disaster risk management and achieving a more integrated approach to improving habitat conditions within vulnerable urban areas. This work demonstrates that vulnerable communities in informal urban settlements can actively address their exposure to risk through locally-oriented, bottom-up collective actions. However, key linkages with institutional frameworks are needed to strengthen state-community dynamics and facilitate sustainable, inclusive and equitable development in cities.